SPINNING SYSTEM NOVELTIES: RECENT INNOVATIONS AND TRENDS (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
The textile industry has undergone significant advancements in spinning technologies, leading to enhanced efficiency, quality, and sustainability in yarn production. Innovations such as compact spinning, rotor spinning, and air-jet spinning have revolutionized traditional methods, offering improvements in yarn strength, reduced hairiness, and higher production speeds. Additionally, the integration of digitalization and automation through Industry 4.0 principles has enabled real-time monitoring and optimization of spinning processes, resulting in reduced defects and improved operational efficiency. Recent developments also emphasize sustainability, with eco-friendly spinning systems that reduce energy consumption and waste. These technological novelties are transforming the spinning sector, providing manufacturers with more versatile, efficient, and sustainable solutions for yarn production.